Human Hunting and Nascent Animal Management at Middle Pre-Pottery Neolithic Yiftah'el, Israel - Sapir-Hen, Lidar (PLoS One, 2016)
The current view for the southern Levant is that wild game hunting was replaced by herd management over the course of the Pre-Pottery Neolithic B period, but there is significant debate over the timing, scale and origin of this transition. To date, most relevant studies focus either on wild game exploitation in the periods prior to domestication or on classic markers of domestication of domestic progenitor species over the course of the PPNB. We studied the faunal remains from the 2007–2008 excavations of the Middle PPNB (MPPNB) site of Yiftah’el, Northern Israel. Our analysis included a close examination of the timing and impact of the trade-off between wild game and domestic progenitor taxa that reflects the very beginning of this critical transition in the Mediterranean zone of the southern Levant. Our results reveal a direct trade-off between the intensive hunting of wild ungulates that had been staples for millennia, and domestic progenitor taxa. We suggest that the changes in wild animal use are linked to a region-wide shift in the relationship between humans and domestic progenitor species including goat, pig and cattle.